Do proton pump inhibitors affect the biomechanical efficiency of implant?- a systematic review - Varsha Verma (Elsevier, 2022)
Abstract-: Purpose: This systematic review was executed to determine the influence of proton pump inhibitors on biomechanical efficiency of dental implants. Materials and methods: The comprehensive online literature search was conducted on digital database of Pubmed, Cochrane database and EBSCO host, Web of Science and Scopus from 2010 to 2021(Dec).The studies included in our research comprised of randomized controlled trials and animal studies. Literature review, Letter to the editor, short communication and studies not related to the dental implants were excluded. A total of 6 studies were finalized and included in the systemic review. Result: The proton pump inhibitors have a negative influence on the bone metabolism and adversely affect the Osseointegration of the dental implants. Further they reduce the biomechanical efficiency of dental implant which ultimately results in their failure. Conclusion: Proton pump inhibitors are a risk factor for dental implant survival. This conclusion has been drawn from the limited research available. Hence well designed prospective randomized controlled trials should be carried out on a large population including the users and non-users, to more thoroughly elucidate the effect of proton pump inhibitor on osseointegration process of dental implants.